2020
DOI: 10.1016/j.buildenv.2020.106779
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a view from a window on thermal comfort, emotion, and cognitive performance

Abstract: Visual connection to nature has been demonstrated to have a positive impact on attention restoration, stress reduction, and overall health and well-being. Inside buildings, windows are the primary means of providing a connection to the outdoors, and nature views even through a window may have similar effects on the occupants. Given that humans recognize environments through multi-sensory integration, a window view may also affect occupants' thermal perception. We assessed the influence of having a window with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(81 citation statements)
references
References 89 publications
6
73
0
2
Order By: Relevance
“…New technologies from medical sciences (e.g., wearable sensors) are gradually being introduced to assess the health aspects of human responses to environmental stimuli or to improve comfort models on the basis of occupants' physiological response [31,32]. Examples of this continuous and ongoing evolution in IEQ research and practice include the development of personal comfort models [32,33] and personal comfort systems [34], the application of circadian lighting design [35], and the valuation of qualitative aspects affecting visual quality [36,37]; but what about acoustics in this "pursuit of wellbeing" [15]?…”
Section: Introductionmentioning
confidence: 99%
“…New technologies from medical sciences (e.g., wearable sensors) are gradually being introduced to assess the health aspects of human responses to environmental stimuli or to improve comfort models on the basis of occupants' physiological response [31,32]. Examples of this continuous and ongoing evolution in IEQ research and practice include the development of personal comfort models [32,33] and personal comfort systems [34], the application of circadian lighting design [35], and the valuation of qualitative aspects affecting visual quality [36,37]; but what about acoustics in this "pursuit of wellbeing" [15]?…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect widely discussed in the literature is the positive distraction caused by nature [33], whereby visual scenes and sounds of nature significantly reduces ratings of pain [34], and influence recovery times from surgery [35] and elevated stress [36]. Ko et al [37] showed positive emotions (e.g., happy, satisfied) were higher and negative emotions (e.g., sad, drowsy) were lower for the participants in a space with window on close nature versus the windowless condition. Herzog and Chernick [38] showed that settings that had distant natural and urban landscapes were perceived as more open (i.e., perceived amount of space).…”
Section: Introductionmentioning
confidence: 99%
“…Another plausible explanation of our findings could be the natural ventilation from window opening (Fisk 2018;Ko et al 2020;Najafi et al 2019). Opening window can increase the indoor infiltration rates and reduce prevalence rates of sick building syndrome (SBS) symptoms (Fisk et al 2009;Fisk 2018).…”
Section: Discussionmentioning
confidence: 88%
“…A recent study also highlighted the beneficial effect of window ventilation for emotion and mood, and it showed that more positive emotions (e. g., happy, satisfied) and fewer negative emotions (e.g., sad, drowsy) for the participants in the window versus the windowless condition. It also suggested that providing a window with a view might boost the comfort, emotion, memory and concentration for the occupants (Ko et al 2020). Additionally, the benefits of higher levels of natural viewing through window- opening might be attributed to the mechanisms of biology, physiology, and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation